PENGARUH MODEL PEMBELAJARAN MISSOURI MATHEMATICS PROJECT (MMP) TERHADAP KEMAMPUAN PENALARAN DAN PEMECAHAN MASALAH MATEMATIKA PADA SISWA MTS JA-ALHAQ KOTA BENGKULU - Ridwanul Fata; Saleh Haji; Hari Sumardi (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
This research aims to determine the influence of the Missouri Mathematics Project (MMP) learning model on the mathematical reasoning and problem solving abilities of Mts Ja-Alhaq students in Bengkulu City. This research uses the Quasi Experiment method. Data collection was carried out through tests. Data analysis used the Ancova test. The sample for this research was MTs Ja-alHaq students in Bengkulu City. The results of the research show that: (1) There is a linear influence of covariates on students' mathematical problem reasoning abilities in learning the Missouri Mathematics Project (MMP) with an influence of 50,7%. (2) There is a linear influence of covariates on students' mathematical problem solving in Missouri Mathematics Project (MMP) learning with a large influence of 14.6%. (3) There is an influence of Missouri Mathematics Project (MMP) learning on students' mathematical problem reasoning abilities with an influence of 78 %. (4) There is an influence of Missouri Mathematics Project (MMP) learning on students' mathematical problem solving abilities with an influence of 55,5%. (5) Students' achievement of mathematical problem reasoning abilities in Missouri Mathematics Project (MMP) learning is better than those taught through conventional learning. (6) Students' mathematical problem solving achievements in Missouri Mathematics Project (MMP) learning are better than those taught through conventional learning